(3JdNjU GdCbhGd aj JMbjb CMhGd GdQLGds - (3GdCSJQBHGOj, eMeO Hf Ydj Hf EHQGgje, J (B1012 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3bO CKHJ ajg GdCSeGA Ydi JQJjH GdMQha GdeYLeI eQGYjG GdChd Ke GdKGfj hgcPG hddCUd ef YOe GdRjGOI MQaG hMQcI (B...s
(3BNQgG (B:s
.. (3hHGdcGXejjf ehSi Hf LYaQ heMeO Hf Ydj GdLhGO Ydjge GdSdGe hGdCUd GdYGe ceG aj JQLeI CHj MGeO GdQGYj hGdMeO ddg QH GdYGdejf (B. (3Jes
(3JHUQI GdYfhGf (B:s
(3aj JMbjb CMhGd GdQLGd , GdQLGd GdhSjWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf (B2/593s
(3GdPQjYI (B4 - 305 (1852)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs